Knowledge of biosafety measures taken by nursing students at a university (2022) - Morales-Aguilar, Rosa Del Socorro; Barraza-Ospino, Damar Paola; Jinete-Acendra, Janeth Cecilia; Ferrer, Ana Manuel; Parody-Muñoz, Alexander Elias (Universidad y Salud, 2025)
Introduction: Biosafety standards knowledge promotes quality and risk-free care for patients and health personnel. Objective: To identify the level of knowledge about biosafety measures in senior students from a Nursing program at a university in Barranquilla, Colombia. Materials and methods: Descriptive cross-sectional epidemiological study with 89 students chosen through a non-probabilistic sampling method. The instrument used was “level of knowledge of biosafety measures in Nursing students.” A Chi-square test (95% CI) was applied to analyze the relationship between the study variables and participants’ level of knowledge. The statistical techniques were performed using version 16 of the Statgraphics statistical software. Results: Medium and low knowledge levels were registered, with percentages of 24.72% and 75.28%, respectively. Furthermore, a minimal difference was observed when the level of knowledge of students was related to academic semesters. Finally, 85% of participants were not cognizant about the concept of hazardous waste. Conclusion: Medium and low levels of knowledge reflect an alarming scenario, which was probably caused by virtual teaching due to the confinement during the COVID-19 pandemic.